Skeletal morphologic features of Anterior Open Bite Malocclusionamongst black patients visiting the Medunsa oral health centre - Sithole, Ntokozo P; Khan, Mohamed I; Sethusa, Mosimane PS (South African Dental Journal, 2020)
INTRODUCTION: Anterior open bite (AOB) malocclusion presents as lack of vertical overlap of anterior teeth. It is viewed to be unaesthetic and may affect speech and mastication It develops due to the interaction of hereditary and environmental etiological factors and these usually affect the vertical growth of the face. This study describes the vertical changes of South African black people presenting with AOB. AIMS AND OBJECTIVES: The aim was to determine skeletal morphological features of patients with AOB malocclusion. DESIGN: The design was a retrospective, cross-sectional study. MATERIALS: Archived pre-treatment lateral cephalographs of 181 patients who consulted between 2007 and 2014 were divided into four groups: control group of 62 patients with skeletal Class I pattern without AOB; test groups of patients with AOB (119) divided into 35 Class I, 43 Class II, and 41 Class III malocclusions. Records of each group were divided according to gender. Descriptive statistics, the Pearson correlation coefficient, t-test and. Wilcoxon test were employed to analyze the data, and p values of <0.05 were considered statistically significant. RESULTS AND CONCLUSIONS: Patients with AOB had a larger vertical facial pattern in all classes of malocclusion. Males presented with larger Sn-GoGn angles than females. The PFH/AFH ratio was lower across all classes of malocclusion compared to the control group.